Peranan subsektor perikanan laut dan budidaya dalam meningkatkan perekonomian Provinsi Riau periode 2007 - 2011 - Budi Apriwinata; Nursiah Chalid; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The fishing sector is divided into two types based on general waters there are fisheries pond, outdoor and marine fisheries and aquaculture. Marine fisheries and aquaculture subsector includes all activities of arrests, seeding and cultivation of all types of salt water fish and other biota. Marine fisheries and cultivation of natural resources including renewable but also potentially depletd because every system environment there is a threshold population size. If the size of a population or stock falls below this limit, then population will perish. Marine fisheries and aquaculture is resource that move and movement is strongly influenced by the physical waters (currents and temperature), lead to this resource in the management strongly depends on the time and season, therefore it is not predictable like other resources. The data used in this study is secondary data coming from various sources, among others the fisheries agency and maritime Province of Riau, the central bureau of statistics of the Province of Riau, that explaines the interconnectedness of marine cultivation and fisheries with the absorption of labour, exports and contributed to the gross regional domestic revenue is seen from time to the time (time series). The result of the study explained that the role of marine fisheries and aquaculture subsector in terms of employment , exports and contribution to regional gross domestic income is relatively small, becaused the marine fisheries and aquaculture is only subsector of fisheries and of course it’s small scope and limited. In addition there are several factors that hinder the development of marine fisheries and aquaculture subsector include economy problems such as difficulty in fuel, global crisis. Besides the weather and pollution issues are also thing that hinder the development of marine fisheries and aquaculture itself.Keywords : Role, Marine Fisheries and Aquaculture Subsector